Education, employment and earnings: a study of the South African manufacturing sector - Pillay, Paramasvaran Narainsamy (School of Economics, 2026)
The thesis has two objectives: First to establish what has happened to employment by the State and the causes behind changes. And second , to establish the role the State has adopted as a labour market operator for white labour and the effects of this role. The work is divided into three parts: PART I: This· establishes some of the economic foundations of the factors affecting State employment. The factors which affect total demand for State employment are those factors which determine the total. demand and supply of public output. There are four interested parties who are affected by the supply of public output: Consumers who demand public output through voting and non-voting pressure; the government which designs public output to suit the median voter and to some extent overcomes the political uncertaintly problem through the implementation of ideology; producers who affect public output through non-voting pressures; and the bureaucracy which produces public output under the criteria of: when a pure public good is produced this is to the full extent of the bureau budget without regard for average and marginal cost conditions and in the production of a pure private good the bureau produces efficiency only if the trading surplus accrues to the bureau PART II: This presents the collected data and discusses problems encountered in the establishment of the data. Employment is presented by race for the various sectors of the State (for example the Central Authorities or the Railways) and for the various types of activity undertaken by the State (for example the provision of Economic Services or Educational Services). PART III: This tackles the two objectives of the work and emerges with -four findings. The most surprising result of the study was while State employment has grown, the growth in black employment was proportionately far greater than the growth in white employment. This growth is largely centred around the growth of black bureaucrats and teaching services in the employ of the Central Authorities in the 1950s and Homeland governments since the 1960s. Second, State employment by activity shows the interesting result that half of all State employment is involved in providing economic services. In 1980, education employment ranked as the second most important type of employment having constituted twenty per cent of State employment. Third, the State views its role as a white labour market operator as that of an 'employer of last resort' for white labour which it achieves by means of always having posts vacant for whites, especially at lower skilled white positions. The results of this are first , to set a minimum wage for whites and second, is likely to cause the State to operate inefficiently. Fourth , it appears that certain sectors of the State were constrained by fixed factor proportions. In the public service, the Railways and the Provincial Administrations, the ratio of black to white employed rarely exceeded 1:1 until very recently. The effect of this has been to limit the growth in employment of some of the sectors as a result of the State difficulties in attracting white labour.